Analysis Bibliometric SME Internationalization Process: Uppsala Model - Ambarwati, Titiek; Sudarmiatin, Sudarmiatin; Sumarsono, Hadi (Publisher Cv. Inara, 2023)
A bibliometric analysis centered on the internationalization process of small and medium-sized firms (SMEs) with the Uppsala Model is presented in this article. The Uppsala model, which was first published in 1977, explains the process by which companies become internationalized. This model has been the subject of extensive research and development over the years. The literature on SME internationalization is investigated in this analysis, with a specific focus on the keywords